Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Simplify the expression:
17 – (-5x + 2)


Sagot :

YujiC

Answer:

5x + 15

Step-by-step explanation:

Let's simplify step-by-step.

17−(−5x+2)

Distribute the Negative Sign:

=17+−1(−5x+2)

=17+−1(−5x)+(−1)(2)

=17+5x+−2

Combine Like Terms:

=17+5x+−2

=(5x)+(17+−2)

=5x+15

Answer:

=5x+15

Answer:

-3

Step-by-step explanation

You would first used distribuve property in the parenthisis.

Because there is a minus sign outside of the parenthisis, it would become (5x-2)

Combine like terms

15+5x=0

Subtract 15 from both sides

5x=-15

Divide 5 to get x

5x(/5)= -15(/5)

x=-3